Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1989
DOI: 10.1002/ca.980020305
|View full text |Cite
|
Sign up to set email alerts
|

Catecholaminergic and peptidergic nerves in naturally occurring and pheochromocytoma‐associated human brown adipose tissue

Abstract: Noradrenergic and peptidergic innervations in naturally occurring and pheochromocytoma-associated human perirenal brown adipose tissue were demonstrated. The presence of both parenchymal and periarterial noradrenergic nerve plexuses was revealed by the sucrose-potassium-glyoxylic-acid (SPG) technique in all tissue samples. Immunohistochemical studies also indicated the presence of neuropeptide Y-like, calcitonin gene-related peptidelike, substance P-like, and bombesinlike immunoreactive nerves in the adventiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1996
1996
1998
1998

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…Furthermore, several studies (Cannon et al, 1986;Lever et al, 1988Lever et al, , 1989Norman et al, 1988) have suggested that some neuropeptides occur in nerves supplying IBAT and PBAT. Thus, the neural control of BAT is more complex than previously thought and includes both sympathetic and sensory nerves (reviewed in HimmsHagen, 1991).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, several studies (Cannon et al, 1986;Lever et al, 1988Lever et al, , 1989Norman et al, 1988) have suggested that some neuropeptides occur in nerves supplying IBAT and PBAT. Thus, the neural control of BAT is more complex than previously thought and includes both sympathetic and sensory nerves (reviewed in HimmsHagen, 1991).…”
Section: Introductionmentioning
confidence: 99%